Soil plug behaviour of open-ended pipe piles during installation. Issue 2 (6th April 2017) - Seo, Hoyoung; Kim, Mintae
Abstract : This study experimentally investigates the effects of the pile diameter and initial soil density on the change of the soil plug state during pile driving through model pile tests. Model piles with two different inner diameters were cut in half vertically and driven along a transparent front wall of a soil tank to visualise the soil plugging process. Loose and dense soils with alternating coloured layers were deposited using fine sand. The entire pile driving process was then recorded using a high-definition digital camera. Detailed image analysis revealed that pipe piles experience repeated transitions from a plugged condition to an unplugged condition during the pile driving process. Compressive strains within the soil plug generally increased with the increasing distance from the top of the soil plug, reached a maximum value and then decreased toward the pile base. Furthermore, the density of the soil plug increased from its initial value and reached a terminal value as the pile penetration increased.